2020
DOI: 10.5194/bg-17-2205-2020
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth elements in oyster shells: provenance discrimination and potential vital effects

Abstract: Abstract. Rare earth elements (REEs) and yttrium in seawater originate from atmospheric fallout, continental weathering, and transport from rivers, as well as hydrothermal activity. Previous studies have reported the use of REE and Y measurements in biogenic carbonates as a means to reconstruct these surface processes in ancient times. As coastal seawater REE and Y concentrations partially reflect those of nearby rivers, it may be possible to obtain a regional fingerprint of these concentrations from bivalve s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The data used in this manuscript have been deposited on the Zenodo data repository (Mouchi et al, 2019).…”
Section: Data Availabilitymentioning
confidence: 99%
“…The data used in this manuscript have been deposited on the Zenodo data repository (Mouchi et al, 2019).…”
Section: Data Availabilitymentioning
confidence: 99%
“…, temperature; Thorrold et al 2007) and metabolism ( e.g. , Mouchi et al, 2020) have been reported to modify the exact seawater composition reflection in biominerals. In species that produce calcified structures at the larval stage, like fish (otoliths) or molluscs (shells), the elemental fingerprint of the larval structure preserved in later developmental stages therefore allows for the determination of their natal geographic origin, provided that the larval calcified structures have been built in sites with differing compositions (Becker et al, 2007; Thorrold et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Deep-sea hydrothermal activity produces massive polymetallic sulphide deposits from the ascent and precipitation of hydrothermal fluids enriched in metals originating from the oceanic crust (Fouquet et al, 1991;Binns and Scott, 1993;Humphris et al, 1995;Hannington et al, 2011). Vent sites are economically interesting to mining companies (Hoagland et al, 2010;Radziejewska et al, 2022), which initiatives are currently under evaluation worldwide (Boschen environmental conditions (e.g., temperature: Thorrold et al, 2007) and animal metabolism (Mouchi et al, 2020). In fish and molluscs, calcified structures produced during the early larval stage and preserved thereafter can be used to infer their natal geographic origin, provided that they have been built in chemically contrasting sites (Becker et al, 2007;Thorrold et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using LA-ICP-MS, we measured rare earth elements and yttrium in oyster shells, as well as their provenance and the potential essential implications of those quantities [15]. An examination utilizing LA-ICP-MS was carried out on 37 blue glass drips unearthed from a tomb in the southern Faiyum district of Egypt [16].…”
Section: Introductionmentioning
confidence: 99%